Online Analytical Processing of Port Calls for Decision Support - Worth, Aidan; Televantos, Aris; Evmides, Nicos; Michaelides, Michalis P.; Herodotou, Herodotos (My University, 2022)
The port call process encapsulates a visitation cycle of a ship to a port and can generate a wealth of data. The real time analysis of port call data can be used to find bottlenecks in the port call process, establish targets based on key performance indicators (KPIs), and to understand how shipping traffic impacts a port's efficiency. This demonstration will showcase a new Power BI interactive report powered by a multidimensional OLAP cube for very fast performance, which is built on top of a data warehouse collecting information from various sources in real time. The report currently visualizes several KPIs and other types of information that can be filtered per port, time-period, vessel type, origin or destination ports, and various other categories to help manage arrivals, departures, and port operations.
Keywords: Key performance indicator; Decision making; Data visualization; Data warehouses; Information filters; Real-time systems; Marine vehicles